Why challenge the ivory tower? New evidence on the basicness of academic patents - Dirk Czarnitzki; Katrin Hussinger; Cédric Schneider (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
While often presumed in academic literature and policy discussions there is little empirical evidence showing that academic patents protect more basic inventions than corporate patents. This study provides new evidence on the basicness of academic patents using German professor patents linked to patent opposition data from the European Patent Office (EPO). Patent oppositions are the most important mechanism by which the validity of patents filed at the EPO can be challenged. Controlling for patent value, asymmetric information and diverging expectations between the opposition parties, the likelihood of a potentially litigious situation and the relative costs of opposition versus settlement, we find that academic patents are opposed less frequently than a control group of corporate patents. This suggests that academic patents cover rather basic inventions with a low immediate commercial value not threatening current returns of potential plaintiffs. The effect is weaker for academic patents in collaboration with the business sector, which suggests that those patents are evaluated as more applied by owners of potentially rival technologies.
Keywords: O31; O32; O34; 330; academic inventors; intellectual property rights; patent oppositions; Hochschulforschung; Erfindung; Patent; Industrielle Forschung; Deutschland